Image-based sexual abuse a study on the causes and consequences of non-consensual nude or sexual imagery - Henry, Nicola; McGlynn, Clare 1970-; Flynn, Asher; Johnson, Kelly ca. 20./21. Jh; Powell, Anastasia; Scott, Adrian J. (Routledge critical studies in crime, diversity and criminal justice, 2021)
"This book investigates the causes and consequences of image-based sexual abuse in a digital era. Image-based sexual abuse refers to the taking or sharing of nude or sexual photographs or videos of another person without their consent. It includes a diversity of behaviours beyond that of "revenge porn", such as blackmail or "sextortion" scams; the use of artificial intelligence to construct "deepfake" pornographic videos; and the taking or sharing of sexual assault imagery. This book investigates the pervasiveness and experiences of these harms, as well as the raft of legal and non-legal measures that have been introduced to better respond to and prevent image-based sexual abuse. The book draws on ground-breaking empirical research, including surveys in three countries with over 6,000 respondents and over 100 victim-survivor and stakeholder interviews. Guided by theoretical frameworks such as gender studies, sociology, criminology, law and psychology, the authors argue that image-based sexual abuse is more commonly perpetrated by men than women, and perpetration is higher among some groups, including younger men and sexuality minority men. The motivations of perpetrators varied, and yet a dominant theme to emerge was that of power and control. The gendered nature of the abuse means that it is best understood as a "continuum of sexual violence" because victim-survivors often experience it as part of a broader pattern of gendered harassment, violence and abuse. Written in a clear and direct style, this book will appeal to students and scholars of criminology, sociology, law and psychology. Image-based sexual abuse is also an essential resource for activists, legal and policy practitioners, technology companies and victim-survivors seeking to understand the deeply complex nature of intimate-image sharing in a digital era"--